Impact of Fracture in Geometrical, Material, and Load Rate Characteristics on J-Integral - Piyush Goyal; Hridyanshu (International Journal of Fracture Mechanics and Damage Science, 2026)
The present study investigates the influence of load rate, geometrical parameters, and material properties on the J-integral behavior of AA2050-T84 aluminum-lithium alloy using three-dimensional elastic–plastic fracture mechanics (EPFM) analysis. Finite element simulations were carried out using the ABAQUS software to evaluate crack driving forces in compact tension (C(T)) specimens under various mechanical and thermal conditions. The study focuses on the combined effects of strain rate, temperature-dependent strain hardening, specimen thickness (B/W ratio), and material anisotropy on J-integral variation along the crack front. A multilinear kinematic hardening material model derived from true stress–strain data was employed to accurately represent plastic deformation behavior. The numerical results were validated through comparison with experimental load versus crack mouth opening displacement (CMOD) curves, confirming the reliability of the developed model. The analysis revealed that the J-integral reaches its maximum value at the crack front center due to crack tunneling effects. Although strain rate showed a positive dependency on J-integral, its influence remained minimal within quasi-static ranges. The results also indicated that J-integral increases with increasing strain hardening ratio and decreases with increasing specimen thickness due to higher constraint effects. Furthermore, anisotropy significantly affected fracture behavior depending on plate orientation and location. These findings provide valuable insights into fracture characterization and structural reliability of Al-Li alloy components used in aerospace structures.
Keywords: AA2050-T84 alloy; ABAQUS simulation; Finite element analysis; J-integral; elastic–plastic fracture mechanics (EPFM)